Nickel heavy metal and dye removal using polyethersulfone microcapsule - Lee, Yu Sin (2024)
The rapid growth of the global population and industrialization has led to increased discharge of organic and inorganic pollutants into water bodies. The wastewater needs to be treated, as it can bring adverse effects to human health. Conventional techniques for removing heavy metals and dyes from wastewater are costly and result in large amounts of sludge. Adsorption is considered as the most efficient wastewater treatment technology due to its reversibility and reusability of adsorbents. Therefore, PES microcapsule have the potential to remove of nickel (Ni) and methylene blue (MB) dye from the water. PES microspheres were synthesized using phase inversion method. Characterization results, such as scanning electron microscopy (SEM), revealed the porous structure of the microcapsules, while Fourier-transform infrared (FTIR) analysis verified the presence of the PES polymer. Thermogravimetric analysis (TGA) demonstrated the outstanding thermal stability of the PES microspheres. The Brunauer-Emmett-Teller (BET) specific surface area of the microcapsules was measured at 10.97 m2/g. Furthermore, the pH drift method proved the presence of a negative charge on the surface of the microcapsules, which can facilitate the removal of cationic pollutants. Response surface methodology based on central composite design (CCD) was used to optimize the effects of different adsorption process parameters such as the pH (4 to 12), microcapsule loading (20 g/L to 40 g/L), and initial concentration (5 mg/L to 25 mg/L for Ni and 1 mg/L to 5 mg/L for MB dye). The optimum Ni removal efficiency was 94.92 % at a pH of 9.98, microcapsule loading of 25.16 g/L and initial concentration of nickel of 20.00 mg/L. Meanwhile, the optimum MB dye removal efficiency was 94.97 % at a pH of 11.99, microcapsule loading of 33.00 g/L and initial concentration of MB of 2.41 mg/L. It was discovered that pH had the highest impact on the removal efficiency, in which it could be improved by increasing the pH of the solution. The presence of Ni and MB dye in the pores of PES microcapsules has demonstrated that the successful adsorption of PES microcapsules was attributed to electrostatic interactions. It can be concluded that PES microspheres are promising adsorbent for removing Ni and MB dye from aqueous solutions, as they exhibited high removal efficiency.